PENGARUH PPN, PPnBM, DAN PKB DENGAN TARIF PROGRESIF TERHADAP DAYA BELI KONSUMEN KENDARAAN BERMOTOR RODA EMPAT DI KOTA SEMARANG - Santoso, Andre Teguh; Ratnawati, Juli (AKUNTANSI DEWANTARA, 2023)
Tax is an obligation paid to the state. Taxes are an obligation for the public. The purpose of this research is to analyze the effect of the imposition of value-added tax, consumption tax on luxury goods, and progressive road tax on consumers' purchasing power. The population in this study were consumers of four-wheeled vehicles at the SAMSAT III Semarang head office. Primary data from the questionnaire and its Slovin sample were used for data collection. Methods of data analysis using multiple regression analysis. VAT has a large positive impact, PPnBM has a large positive impact, and PKB progressive tariffs have a positive impact on purchasing power.